The EFFECT OF NIPPLE STIMULATION ON THE LENGTH OF THE FIRST STAGE AND ACTIVE PHASE IN PRIMIGRAVIDA: PENGARUH RANGSANGAN PUTING SUSU (RPS) TERHADAP LAMANYA KALA I FASE AKTIF PADA IBU PRIMIGRAVIDA - Yena Novia Puspita Herawati; Rifzul Maulina; Rani Safitri (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Introduction: During the process of childbirth there are several stages, one of which is stage I of delivery. There is a difference in the length of the first stage in primigravida mothers and multigravida mothers. In primigravida mothers, the first stage will take longer due to the mother's lack of experience in handling childbirth. The delivery process will not experience obstacles if the contraction is good and does not weaken. One action that can be taken to increase uterine contractions naturally is by providing nipple stimulation. Nipple stimulation is the act of giving a light massage to one of the nipples using your fingers. The purpose of giving nipple stimulation is to release the hormone oxytocin which can cause contractions during the birth process. Aims: This study aims to determine the effect of nipple stimulation on the length of the first stage of active phase in primigravida.Method: The research carried out by this researcher is a type of quantitative research using quasi-experimental research methods and using a posttest only control group design. The sample used in this study was 16 primigravida mothers who were divided into 2 groups as the control group and the subjects. The sampling technique used is purposive sampling. Data analysis using the Mann-Whytney test. Result and Conclusion: After analyzing the data, the p-value was 0.02, which means the research results had a p-value <0.05. This shows that nipple stimulation has an influence on the length of the first stage of primigravida.